Spanish Translation, Cultural Adaptation, and Validation of the Standardized Cosmesis and Health Nasal Outcomes Survey Questionnaire (2019)
Background: The Standardized Cosmesis and Health Nasal Outcomes Survey (SCHNOS) questionnaire is a new instrument that was developed to evaluate both functional and cosmetic components of rhinoplasty. It is a reliable, consistent, and validated patient-reported outcome measure that is not available in Spanish. Methods: The SCHNOS questionnaire was forward translated, back translated, and culturally adapted following international guidelines. Its psychometric validity was tested with native Spanish speakers in 2 centers in Colombia. The authors measured internal consistency, correlation, and reproducibility to determine validity of the instrument. Results: The final Spanish version of the SCHNOS was administered to 76 native Spanish speakers. Both the SCHNOS-O (obstructive domain) and SCHNOS-C (cosmetic domain) showed a high internal consistency with Cronbach’s alpha of 0.84 and 0.94, respectively. The Spearman correlations between the items of SCHNOS-O (0.38–0.82) and SCHNOS-C (0.49–0.88) were positive and significant. Spearman’s rank correlation in the test–retest analysis for SCHNOS-O (r = 0.87) and SCHNOS-C (r = 90) was positive and statistically significant. There was statistical significance in responses obtained for SCHNOS-O (P < 0.001) but not for SCHNOS-C (P = 0.222). Conclusions: In this study, the SCHNOS was successfully translated and culturally adapted into Spanish. The Spanish version of the SCHNOS was shown to be a reliable and valid instrument that we recommend it should be used in Spanishspeaking patients who are having functional or cosmetic rhinoplasty.